A green development model: transnational model-making in China's small hydropower training programmes. Issue 3 (2nd September 2017) - Harlan, Tyler
ABSTRACT: The expansion of Chinese overseas investment and aid over the past decade has triggered concern that China is 'exporting' an environmentally destructive development model to other countries. Yet China's foreign aid also includes training programmes in 'green' technologies, such as small hydropower (SHP). This paper analyzes the policies, technologies and ideas around green development that these training programmes promote, and their political and commercial benefits for Chinese actors. It frames training courses and the technology transfer activities that follow as transnational model-making in that they situate SHP as a green model that is an aspect of China's modernization. This helps to improve China's developmental reputation and promote its SHP industry and water infrastructure.